Ecological-epidemiologic and prognosis of the morbidity of countryfolk by malignant neoplasms - A. G. Gasangadjiyeva; G. M. Abdurakhmanov; P. I. Gabibova (Юг России: экология, развитие, 2015)
This work is devoted in the research of the basic tendencies, dynamics, territorial features and the forecast malignant neoplasm morbidity of the population of countryside of republic Dagestan.